Effect of refugia plant (Zinnia sp.) population on the presence of stem borer (Scirpophaga innotata Walker) and natural enemies in rice - OLSIVIANA OLSIVIANA; AMIR YASSI; MELINA MELINA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Olsiviana, Yassi A, Melina. 2024. Effect of refugia plant (Zinnia sp.) population on the presence of stem borer (Scirpophaga innotata Walker) and natural enemies in rice. Biodiversitas 25: 2652-2660. This study supports biological control by preserving natural enemies in rice cultivation through habitat modification. The research aimed to analyze the effects of different population levels of refugia (Zinnia sp.) on pest attack rates, the presence and diversity of natural enemies of rice stem borer (Scirpophaga innotata Walker 1863), and rice (Oryza sativa L.) production. The study was designed using a Randomized Group Design (RGD) with four population treatment levels: control (no Zinnia sp.), sparse population (32 polybags of Zinnia sp.), medium population (96 polybags of Zinnia sp.), and dense population (160 polybags of Zinnia sp.). The results showed that the dense population (160 polybags of Zinnia sp.) produced the lowest stem borer infestation rate in the eighth week of observation (1.67%). Pests in all treatments belonged to four orders: Lepidoptera, Hemiptera, Coleoptera, and Diptera, with Hemiptera being the most prevalent. Natural enemies of rice pests belonged to three orders: Coleoptera, Hymenoptera, and Orthoptera. The dense population treatment (160 polybags of Zinnia sp.) yielded the highest values for diversity index (H') at 2.1785, species richness index (R) at 2.1837, and evenness index (E) at 0.9915. This treatment also achieved the highest average rice production at 8.64 tons/ha. Meanwhile, the highest dominance value (C) of 0.2489 was found in the control treatment. Thus, this study supports the idea that increasing the population of Zinnia sp. as a refugia plant can increase the diversity of natural enemies, reduce rice stem borer infestation, and increase rice plant production.